KRISIS IDENTITAS ARAB PADA TUTURAN ALIH KODE DAN CAMPUR KODE BARA MASOUD - Astari, Rika; Mutiawati, Dela; Faturrahman, Muhammad Irfan (Arabi : Journal of Arabic Studies, 2021)
There has been an identity crisis as an Arabic derivative in the speech of code switching and code mixing in Bara Masoud's Instagram caption. This study aims to show the forms of code switching and code mixing in BM's Instagram caption, the factors and their impact on BM's identity as Palestinian Arab descent. This research is descriptive qualitative. The data of this research is Baara Masoud's Instagram caption (May-July 2021). The identity crisis shown by code switching and code mixing into English has emphasized that language control and public understanding processes are needed on the characteristics of language and national identity in interacting on social media. English characters which consist of: not distinguishing between feminine and masculine verbs, social status, simple syllables, which are suitable for use by teenagers have become one of the causes of shifting a language to a cultural values and the identity of a nation.